A Case of Kikuchi's Disease Without Cervical Lymphadenopathy. (5th December 2022) - Tomori, Shinya; Korematsu, Seigo; Momose, Taichi; Urushihara, Yasuko; Momose, Shuji; Moriwaki, Koichi
Abstract : Background . Kikuchi's disease with only extracervical lymphadenopathy is rare. Case Presentation . A 15-year-old male has presented with a fever lasting more than 1 week and right axillary lymphadenopathy. An axillary lymph node biopsy revealed coagulation necrosis, nuclear decay products, infiltration of histiocytes, and enlarged lymphocytes; he was diagnosed with Kikuchi's disease. The only four adult patients with Kikuchi's disease presenting without cervical lesions have been previously reported. Conclusion . This is the only pediatric case of Kikuchi's disease presenting without cervical lymphadenopathy. Kikuchi's disease should be included in the differential diagnosis even in cases of extracervical lymphadenopathy alone.